Birds of a Feather Don’t Always Flock Together: User Problems in Identifying Headwords in Online English Learner’s Dictionaries - Miller, Julia (Lexikos, 2013)
Idioms, sayings and proverbs (referred to here as ’phrasemes’), are a central part of the English language. However, it is often difficult for learners of English as an Additional Language (EAL) to choose the correct headword when looking for such expressions in a dictionary. Learners may not recognise a word as belonging to a phraseme, and so may not look under a single, ’important’ word. Moreover, their choice of a salient word may not accord with the lexicographer’s. Thirdly, they may not recognise phraseme variants, such as carry/take coals to Newcastle. They may therefore often fail to find the phraseme altogether. A study of 84 phrasemes in five online English learner’s dictionaries (Cambridge Advanced Learner’s Dictionary, Collins COBUILD Advanced Dictionary, Longman Dictionary of Contemporary English, Macmillan English Dictionary for Advanced Learners and Oxford Advanced Learner’s Dictionary) revealed a lack of uniformity across and often within dictionaries. This paper is based on 14 of these phrasemes, which appear in one or more of these dictionaries and include proper nouns and/ or variable words. To make learner’s dictionaries more user friendly (Zgusta 1971), it is argued that they need greater consistency in their choice of phraseme headwords, both within and between dictionaries, and that greater cross-referencing is necessary within a single dictionary. Five strategies are presented to help learners with their dictionary searches.